Senior High School Teachers’ Readiness In Implementing 21st Century Learning: An Input To School Improvement Plan - Buenvinida, Lerma P.; Rodriguez, Maria Teresa M.; Sapin, Sherwin B.; Alforja, Nilda S.; Panopio, Francisco P. (Advances in Social Sciences Research Journal, 2020)
This study aimed to identify the level of teachers’ readiness in implementing the 21st century learning; determine the relationship between teachers’ demographic profile and level of understanding 21st century learning; determine the difference between Bay and Los Baños districts teachers’ readiness; and design a training program for teachers. The respondents were the regular/permanent senior high school teachers of the Department of Education in the said districts, School Year 2019-2020. The teacher-respondents were from three and six public senior high schools from Bay and Los Baños, Laguna, respectively; adopted questionnaire and used simple random sampling technique. Findings, reveal that the level of teachers’ readiness was high but they still need professional development in order to: increase the knowledge about 21st century learning; assessment of students, use technology as a tool in teaching; and have advanced training on different strategies in handling 21st century students. The teachers’ profiles such as sex, age, teaching position, years in service and educational attainment influenced the level of teachers’ understanding in implementing the 21st century learning; while there is no difference on teachers’ level of readiness between the Bay and Los Baños districts. Hence, a comprehensive training program is recommended to enhance teachers’ professional and technical skills.